?MEASUREMENT OF MAJOR AMBIENT AIR POLLUTION COMPONENTS AT SUB-URBAN AREA OF KARACHI - Yousufzai, A H K; Hashmi, Durdana Rais (Biological Sciences - PJSIR, 1999)
Base line study for the measurement of major ambient air pollution components such as 0.1, SOl, CO, NO, NOx, PM I0, methane, non-methane along with the meteorological parameters was carried out by Air pollution Monitoring Mobile Laboratory at an urban back ground site of Karachi. The average concentration of 0, was found to be between 4.62 and 20.36 ppb. S02 0.73 and 4.69 ppb, CO 0.14 and '0.77 ppill. NO 0.92 and 2.73 ppb. NOx 3.1 and 7.5 ppb, PMIO 142 and 251 ug rn', methane 1.09 and 2.7 ppm, non-methane hydrocarbon 0.41 and 0.96 ppm.